New Organic PathumThani1 Rice Planting with Biofertilizer Mixed with Nano Microbe for Large Plots of Community Networks: A Case Study in Nong Suea District, Pathum Thani Province - Rattanaloeadnusorn, Sukhan; Tamsamak, Nisarat; Rattanalertnusorn, Atchanut (Recent Science and Technology, 2023)
This research demonstrated a new concept of using biofertilizer mixed with nano microbe inoculants in large plots, collaborated with a Large Plots of Community network of learning centers of increasing production efficiency of agricultural products in Nong Suea District, Pathum Thani Province. The experiment was designed by using Complete Randomized Design (CRD). The control group was urea chemical fertilizers (T0), while the experiment group: biofertilizer mixed nano-microbial concentrate Trichoderma Beuvaria and Metharhizium and 0.3 % organic extracts (T1) and organic fertilizers (T2). T1 showed the greatest treatment compared to other treatments. T1 helped increase paddy yield to 1,137.50 ± 47.87 kg/rai, reduce total costs to 2,250 ± 57.74 bath/rai, increase income 12,125 ± 853.91 bath/rai. In addition, T1 affected the soil to pH 6.00 ± 0.58, increased soil microbial diversity to 14.33 ± 5.26 genus and reduce mercury in rice 9.28 ± 0.081 mg/. T2 could increase paddy yield at 800 ± 43.97 kg/rai, reduce total costs to 2,300 ± 81.65 bath/rai, increasing income 6,550 ± 57.74 bath/rai. It also adjusted soil pH 5.13 ± 0.63, increasing soil microbial diversity 4.33 ± 0.70 genus, reducing mercury in rice 20.16 ± 0.23mg/l, and could be grown by using chemical urea fertilizers, respectively at 0.05 significant. These could be because microbial fungi on organic matter with positive ions (cations), which could bind to negative ions (anions). The antagonist microbial secreted enzymes and accelerated organic degradation into macronutrients, micronutrients and nutritional supplements, sugar, hormones, amino acids, chelates, proteins, vitamins, minerals that the root cells could absorb nutrients and organic extracts into cells quickly, reduce the loss to the environment and adjust the soil pH. Therefore, the learning centers for increasing production efficiency of agricultural products in Nong Suea district, Pathum Thani Province with participation of the network Rajamangala University of Technology Thanyaburi were expanded for Pathum Thani 1 rice planting area, together with the biofertilizers mixed with nano-microbe inoculants Trichoderma Beuvaria and Metharhizium and 0.3 % organic extracts leading to success and strengthening in a sustainable identity.